Oak and others, new to Poland, hosts of mistletoe Viscum album subsp. album in the city of Toruń and its immediate vicinity - Rutkowski, Lucjan; Nienartowicz, Andrzej; Kunz, Mieczysław (Ecological Questions, 2023)
The paper presents the distribution of localities of seven tree taxa, identified as new hosts of mistletoe in Poland, in the city of Toruń. Particular attention was paid to the description of a site with mistletoe on an oak identified as Quercus x rosacea. The reason for this is that native oaks are rare hosts of mistletoe in Central and Eastern Europe and this is the first finding of such a host–parasite association in Poland. The occurrence of all eight host species at 14 sites was compared with the distribution and description of localities and morphological characteristics of both host–mistletoe association components presented in the botanical, ecological and forestry literature.